Implementación de un sistema híbrido eólico-solar para la generación eléctrica en la hacienda Barrancas de la empresa "Novopan" del Ecuador S.A de la provincia de Cotopaxi. - Angulo Ruiz, Estefanía Monserrath (2018)
At Cotopaxi province is located the Barrancas Hacienda of NOVOPAN del Ecuador S.A company which does not have electricity as it is isolated from the electricity supply network, so the objective of this technological proposal as part of an institutional agreement with this company is the generation of electricity from renewable energy sources to get the demand of 1200 daily Watts which is the maximum electricity consumption of the hacienda, for this researching has been conducted on how to generate this energy by collecting and using speed data of the wind and solar radiation available in this sector the same as after the collection, analysis, application of equations and techniques have resulted in solar radiation is 4719,61 Wh/m^2/día and the average speed of the wind is 7.9057 m / s, from this the sizing of equipment and the implementation of a hybrid system wind-solar for the electrical generation in the hacienda Barrancas of the company "NOVOPAN" of Ecuador S.A of Cotopaxi province and in this way the demand of electrical energy required was stored by storing it in accumulation systems so that it can be used without inconveniences.